2006
DOI: 10.1186/1740-3391-4-16
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythm of salivary and serum urea concentration in sheep

Abstract: BackgroundIn domestic animals many biochemical and physiological processes exhibit daily rhythmicity. The aim of the present study was to investigate the rhythmic pattern of salivary and serum urea concentrations in sheep.MethodsSix 3-year-old female sheep kept in the same environmental conditions were used. Sheep were sampled at 4 hour intervals for 48 consecutive hours starting at 08:00 of the first day and finishing at 04:00 of the second day. Blood samples were collected via intravenous cannulae inserted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
1
12
2
Order By: Relevance
“…In the same animals the acrophases of serum urea were recorded at 11:40 hours and 12:24 hours, on days 1 and 2 respectively, and it is important to emphasise that animals were fed once daily at 07:00 hours. These acrophases are similar to those found in sheep under the same natural photoperiod and feeding regimen 11 . The highest concentration of urea reached in the saliva follows that reached in the blood.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the same animals the acrophases of serum urea were recorded at 11:40 hours and 12:24 hours, on days 1 and 2 respectively, and it is important to emphasise that animals were fed once daily at 07:00 hours. These acrophases are similar to those found in sheep under the same natural photoperiod and feeding regimen 11 . The highest concentration of urea reached in the saliva follows that reached in the blood.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, saliva is an appropriate specimen in fields such as physiology, psychology, sports medicine, pharmacology, immunology, paediatrics and geriatric medicine 5–7 . In veterinary medicine, only a few studies of saliva have been carried out, mostly in sheep, 8–10 whereas chronophysiological studies of human saliva are widely documented 11–13 . Therefore, the aim of the present study was to define non‐invasive experimental protocols for animals and to underline the importance of saliva samples as the main or complementary diagnostic means in veterinary chronophysiology.…”
mentioning
confidence: 99%
“…In pigs, a decrease of free fatty acids in serum was seen within 1 h after feeding (Houpt et al, 1986), and insulin in plasma was found to increase postprandial (Koopmans et al, 2005). Moreover, plasma urea varies throughout the day in relation to the time of feeding (Gustafsson and Palmquist, 1993;Rodriguez et al, 1997;Piccione et al, 2006). In sheep, Caldeira et al (1999) published variation of most routine analytes depending on feeding time and level of feed intake; however, in this study, ewes had access to food just once a day, which may not be comparable with ordinary conditions, for example, at pasture.…”
Section: Animal-related Changesmentioning
confidence: 92%
“…Because the deamination of amino acids produces levels of ammonia that could be life threatening, its elimination via conversion to urea is essential for survival. Proteomic analysis reveals that members of the urea cycle oscillate in the liver (14,28), and urea has been reported to oscillate in the blood of several species (28,(61)(62)(63)(64)(65). As blood flow into the liver is a circadian event, it is possible that some metabolites represent physiological oscillations that are independent of hepatocyte production; however, these still reflect the changing diurnal landscape of hepatic metabolism.…”
Section: Discussionmentioning
confidence: 99%